2012
DOI: 10.2478/v10295-012-0032-5
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Effects of Vetiver Grass (Chrysopogon zizanioides) Strips, Vetiver Mulch and Veticompost on Soil Quality and Erodibility of a Sloping Land

Abstract: This study investigates the influence of vetiver grass strips (VGS), vetiver mulch (VGM) and composted vetiver prunes (veticompost) on soil quality of an eroded land in the Institute of Agricultural Research and Training, Ibadan (7 0 22 ' N; 3 0 50 ' E), Nigeria. The treatments were 3-m wide VGS established at 10-m inter-row spacing, VGM imposed at 5 Mg ha-1 , veticompost applied at 5 Mg ha-1 and a control (no-vetiver grass). All quality indicators including physical, chemical and biological indices and soil e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…In the present study, the bulk density of the control plots was significantly higher (P<0.05) compared to the bulk density of the biochar treated plots. A number of studies at both the field and laboratory scale, have reported that manure addition reduces the soil bulk density (Ota et al, 2018a;Are et al, 2012). For instance, research conducted by Ojeniyi et al (2013) at Akure, Nigeria, on sandy loam soil found that 5 t ha -1 of poultry manure reduced the soil bulk density by 13.9 % (Ojeniyi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the bulk density of the control plots was significantly higher (P<0.05) compared to the bulk density of the biochar treated plots. A number of studies at both the field and laboratory scale, have reported that manure addition reduces the soil bulk density (Ota et al, 2018a;Are et al, 2012). For instance, research conducted by Ojeniyi et al (2013) at Akure, Nigeria, on sandy loam soil found that 5 t ha -1 of poultry manure reduced the soil bulk density by 13.9 % (Ojeniyi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Vetiveria zizanioides is a perennial herbaceous plant of the Poaceae family, which has a developed root system, wide adaptability, strong tolerance to environmental conditions, and rapid growth. It is often used in the ecological restoration of coal mine wasteland, as it can not only grow in poor habitats such as tailings waste created during product separation [11][12][13], but can also absorb and accumulate copper, zinc, lead, chromium, and nickel at thresholds of 15 mg/kg, 880 mg/kg, 78 mg/kg, 5-18 mg/kg, and 347 mg/kg, respectively [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%